Characterization of various bitumen exposed to environmental chemicals. (20th February 2022) - Zhang, Xuemei; Hoff, Inge; Chen, Hao
Abstract: As a necessary element of asphalt concrete, bitumen plays a decisive role in influencing the durability and lifespan of asphalt pavement. Environmental chemicals, such as de-icing salt and acid rain, have negative effects on asphalt pavement. However, different bitumen might react differently to environmental chemicals. The purpose of this research is to investigate the influence of environmental chemicals on various bitumen. To achieve this goal, three types of bitumen, base bitumen, polymer modified bitumen, and rejuvenated bitumen, were submerged in three environmental chemicals (sodium chloride, calcium chloride, and acid). The micro-surface, physical properties (penetration, softening point, and dynamic viscosity), low-temperature rheological properties (creep flexural stiffness and relaxation rate), moderate-temperature rheological properties (complex modulus and phase angle), and mechanical properties (non-recoverable creep compliance, recovery percent, and fatigue life) of bitumen were characterized by scanning electron microscopy, physical tests, bending beam rheometer, and dynamic shear rheometer. The chemical bond of three kinds of bitumen was characterized by mean of Fourier transform infrared radiation spectrometer to analyse the reaction between various bitumen and chemicals. Three types of bitumen performed differently to environmental chemicals due to different reactions. The oxidation, stabilization, and polymerization of base bitumen occurred during the chemical process, which leads to apparent changes in bitumen performance. The combination of decomposition and oxidation of polymer modified bitumen lowered the ageing degree and induced the different trend in softening point, dynamic viscosity, non-recoverable creep compliance, and recovery percent. With the addition of the rejuvenator, the effect of environmental chemical on rejuvenated bitumen was reduced. Therefore, polymer modified bitumen had the best resistance to environmental chemicals, followed by rejuvenated bitumen, base bitumen had the worst chemical resistance. Moreover, sodium chloride, calcium chloride, and acid caused the most significant change of base bitumen, polymer modified bitumen, and rejuvenated bitumen, respectively. These findings of this research help engineers understand the effect of environmental chemicals on bitumen performance and select proper bitumen type under different chemical conditions.